Investigating Gray and White Matter Structural Substrates of Sex Differences in the Narrative Abilities of Healthy Adults - Angelopoulou, Georgia; Meier, Erin L.; Kasselimis, Dimitrios; Pan, Yue; Tsolakopoulos, Dimitrios; Velonakis, George; Karavasilis, Efstratios; Kelekis, Nikolaos L.; Goutsos, Dionysios; Potagas, Constantin; Kiran, Swathi (Frontiers in Neuroscience, 2020)
Linguistic aspects of narration have been investigated in healthy populations, in a variety of languages and speech genres with very different results. There is some evidence indicating that linguistic elements, such as speech rate, mean length of utterance, frequency of nouns and verbs, might be affected by non-linguistic factors such as sex. On the other hand, despite the existence of neuroimaging evidence of structural differences between males and females, it is yet unknown how such differences could explain between-sex disparities in linguistic abilities in natural speech contexts. To date, no study has evaluated discourse production elements in relation to sex differences and their neural correlates in terms of brain structure, a topic that could provide unique insights on the relationship between language and the brain. The aim of the present study was to determine sex differences in narrative skills in healthy adults and to investigate white and grey matter structural correlates of linguistic skills in each group. Twenty-seven male and 30 female right-handed, neurologically-intact, speakers, matched for age and years of education, participated. Narrations of a personal medical event were elicited. Linguistic elements of speech rate, mean length of utterances, frequency of nouns and verbs were calculated for each speech sample, by two independent raters. 3D T1 images were segmented and parcellated using FreeSurfer. Between-group differences in white matter diffusion tensor scalars were examined via TBSS and whole-brain tractography and automated tract delineation using AFQ. Speech rate and noun frequency were significantly lower for men, while verb frequency was significantly higher for women, no differences were identified for mean length of utterance. Regarding cortical measures, males demonstrated increased volume, surface area and cortical thickness in several bilateral regions, while no voxel-wise or tractography-based between-group differences in white matter metrics were observed. Regarding the relationship between sex and speech variables, hierarchical regression analyses showed that the superior frontal cluster in surface area may serve as a significant predictor of speech rate, but only in females. We discuss possible interpretations of how sex-related speech abilities could be represented differently in men and women in grey matter structures within the broad language network.